Ordered macroporous carbon-supported bimetallic monatomic catalyst, and preparation method and application thereof
By using an ordered macroporous carbon-backed bimetallic single-atom catalyst in zinc-air batteries, the problems of low catalytic activity and poor stability of existing catalysts are solved, and efficient oxygen reduction reaction and long-life battery performance are achieved.
Patent Information
- Application Number
- CN202411915501.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The existing air electrode catalysts have problems such as low OER/ORR dual-function catalytic activity, slow reaction kinetics, poor stability and low mass transfer efficiency in zinc-air batteries, resulting in low battery energy efficiency, low energy density/power density and short service life.
The catalyst is prepared by synthesis of polymer microsphere templates, filling transition metal precursors, calcining and mixing aging, and forming a heterobimetal monoatomic layer of core-shell structures, synthesizing the oxygen reduction reaction.
The efficiency of oxygen reduction reaction is significantly improved, the intrinsic catalytic activity and stability of the catalyst is improved, the number of active sites is increased, the three-phase interface of gas-liquid-solid is optimized, and the output power density and cycling durability of zinc-air batteries are improved.
Smart Images

Figure CN119852426A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of fuel cells and metal-air batteries, and in particular to an ordered macroporous carbon-supported bimetallic single-atom catalyst, a preparation method and application thereof. Background Art
[0002] Metal zinc-air batteries have high energy density (1086Wh kg -1 ), high intrinsic safety, low manufacturing cost, rich metal zinc resources, and environmental friendliness. It has great application prospects in consumer electronics, communication base stations, power batteries, smart grids, and industrial and commercial energy storage, and has received widespread attention. Metal zinc-air batteries are usually composed of a metal zinc negative electrode, a diaphragm, an air electrode, and an electrolyte. The metal zinc negative electrode and the air electrode generate current through redox reactions. As the core component of zinc-air batteries, the air electrode performs the oxygen reduction / oxygen evolution reaction (ORR / OER) catalytic function during the battery charge and discharge process, and plays a decisive role in the comprehensive performance of zinc-air batteries, such as discharge capacity, energy density, power density, and service life.
[0003] At present, air electrode catalysts still face major challenges such as low OER / ORR bifunctional catalytic activity, slow reaction kinetics, poor stability, and low mass transfer efficiency, which lead to bottleneck problems such as low battery energy efficiency, low energy density / power density, and short service life, seriously restricting the commercial application of zinc-air secondary batteries.
[0004] The air electrode catalysts currently under development mainly include three categories: carbon material systems, transition metal compounds, and transition metal / carbon-based composite systems. Single-atom catalysts maximize the utilization of active metals and greatly increase the content of metal-nitrogen coordination at active sites in the material. At the same time, the strong interaction between metal atoms and carbon carriers can promote the ORR / OER reaction to a four-electron process. It has shown great application potential in the field of zinc-air batteries and has received widespread attention.
[0005] However, the structure of monometallic single-atom catalysts is relatively simple and lacks coordination between atoms. It is difficult to break the linear relationship between the adsorption energies of reaction intermediates and achieve excellent ORR / OER catalytic activity by simply regulating the type of central metal atoms, atomic coordination structure, and carrier structure. Bimetallic single-atom catalysts can achieve higher metal loading and more flexible active site structures by constructing bimetallic active sites. At the same time, heteronuclear bimetals with asymmetric adsorption sites can directly adjust the d-band electronic structure and the spin state density of the active center, thereby achieving the optimal adsorption energy with the intermediates, greatly improving the bifunctional oxygen electrocatalytic performance and stability.
[0006] In addition, the ORR / OER reaction of zinc-air batteries involves a gas-liquid-solid three-phase interface, and the pore structure of the air electrode has an important influence on the mass transfer efficiency and battery performance. The ordered hierarchical macroporous structure has excellent mass transfer capacity. Its high porosity can provide an efficient transmission channel for the rapid transmission of gas and liquid; the high specific surface area can provide a gas-liquid-solid three-phase reaction area, increase the number of effective catalytic active sites, and promote electron transfer.
[0007] Therefore, the technical problem that needs to be solved urgently is to provide an ordered macroporous carbon-supported bimetallic single-atom catalyst to enhance the application value of zinc-air battery performance. Summary of the invention
[0008] The present invention is made to solve the above-mentioned problems, and aims to provide an ordered macroporous carbon-supported bimetallic single-atom catalyst, a preparation method and an application thereof.
[0009] The invention provides a method for preparing an ordered macroporous carbon-supported bimetallic single-atom catalyst, which has the following characteristics and comprises the following steps: S1, synthesizing a polymer microsphere template, preparing a first transition metal-organic precursor solution, and placing the polymer microsphere template in the first transition metal-organic precursor solution for immersion at room temperature for 2 hours to obtain a product A; S2, vacuum degassing the product A, then filtering and drying it in a 40-60°C oven overnight, and vacuumizing it in a solution with a volume ratio of ammonia water to methanol of 1:(0.8-1.2). Degas in air for 20-40 minutes, then impregnate at room temperature for 20-30 hours, filter to obtain the impregnated template, and dry it in an oven at 40-60°C overnight to obtain a microsphere template filled with the precursor; S3, place the microsphere template filled with the precursor liquid in a tubular furnace, introduce inert gas, calcine to obtain product B; S4, mix product B with the second transition metal precursor liquid, age, centrifuge, dry, and place in a tubular furnace, introduce inert gas, heat to 600-1000°C at 3-7°C / min, and calcine for 2-4 hours.
[0010] In the preparation method of the ordered macroporous carbon-supported bimetallic single-atom catalyst provided by the present invention, it can also have the following characteristics: wherein, the metal ions in the first transition metal-organic precursor and the second transition metal-organic precursor are selected from two or more of the transition metals cobalt, iron, zinc, iron, copper, nickel, manganese, platinum, ruthenium, and iridium, the metal ion concentration is 60-200mmol / L, and the first transition metal-organic precursor solution includes at least one of 2-methylimidazole, dopamine hydrochloride, pyrrole and dicyandiamide.
[0011] In the preparation method of the ordered macroporous carbon-supported bimetallic single-atom catalyst provided by the present invention, it can also have the following characteristics: wherein, the polymer microsphere template is a polystyrene sphere template, and the preparation method of the polystyrene sphere template is as follows: take 4-6%wt polystyrene microsphere emulsion in a centrifuge tube, centrifuge it for multiple times at a speed of 12000-18000 rpm, remove the supernatant and place it in a 40-80℃ oven to dry overnight.
[0012] In the preparation method of the ordered macroporous carbon-supported bimetallic single-atom catalyst provided by the present invention, it can also have the following characteristics: wherein, the calcination method in step S3 is to heat to 350-450°C at 3-7°C / min and calcine for 4-6h, and then heat to 900-940°C at 3-7°C / min and calcine for 2-4h.
[0013] In the preparation method of the ordered macroporous carbon-supported bimetallic single-atom catalyst provided by the present invention, it can also have the following characteristics: wherein, the mixing and aging step in step S4 is specifically as follows: product B is dispersed in ethanol to obtain dispersion A, anhydrous ferric chloride, cyanuric acid, and dopamine hydrochloride are dispersed in ethanol and water to obtain dispersion B, dispersion B is poured into dispersion A, and after adding ammonia water, it is stirred and aged at room temperature for 10-14 hours, the mass ratio of anhydrous ferric chloride, cyanuric acid and dopamine hydrochloride is 1:(9-11):(1-1.5), and the mass ratio of dispersion A to dispersion B is 1:(5-5.5).
[0014] The present invention also provides an ordered macroporous carbon-supported bimetallic single-atom catalyst, which has the following characteristics: it is prepared by the above-mentioned method for preparing the ordered macroporous carbon-supported bimetallic single-atom catalyst.
[0015] The ordered macroporous carbon-supported bimetallic single-atom catalyst provided by the present invention may also have the following characteristics: wherein, the three-dimensional porous nitrogen-doped carbon anchoring the first transition metal and the carbon-supported second transition metal single-atom layer coated on the surface of the three-dimensional porous nitrogen-doped carbon substrate, the three-dimensional porous nitrogen-doped carbon and the carbon-supported second transition metal single-atom layer have heterogeneous transition metal single atoms, the inner and outer parts form a core-shell structure, and the dual active metal atom sites synergistically catalyze the oxygen reduction reaction.
[0016] The present invention also provides an application of an ordered macroporous carbon-supported bimetallic single-atom catalyst in a zinc-air battery.
[0017] In the application of the ordered macroporous carbon-supported bimetallic single-atom catalyst provided by the present invention in a zinc-air battery, the zinc-air battery may also have the following characteristics: wherein the zinc-air battery comprises a positive electrode sheet, a negative electrode sheet, a diaphragm, an air inlet and an electrolyte, the catalyst of the positive electrode sheet is an ordered macroporous carbon-supported bimetallic single-atom catalyst, the positive electrode sheet and the negative electrode sheet are placed opposite to each other, the positive electrode sheet and the negative electrode sheet are separated by a diaphragm, wherein the side of the positive electrode sheet having the ordered macroporous carbon-supported bimetallic single-atom catalyst faces away from the air inlet.
[0018] In the application of the ordered macroporous carbon-supported bimetallic single-atom catalyst provided by the present invention in the zinc-air battery, it can also have the following characteristics: wherein the material of the negative electrode sheet is zinc foil, the separator is glass fiber paper, and the electrolyte is potassium hydroxide and zinc acetate aqueous solution.
[0019] Functions and Effects of the Invention
[0020] According to the ordered macroporous carbon-supported bimetallic single-atom catalyst, preparation method and application involved in the present invention, the composite structure of special bimetallic single atoms greatly enhances the intrinsic oxygen reduction reaction activity of the single-atom catalyst derived from the traditional zeolite imidazole framework (ZIF), the high specific surface area of the ordered hierarchical macroporous structure provides more accessible active sites, and the rich pore structure is more conducive to the formation of an effective three-phase interface and rapid mass transfer in the electrochemical process. These characteristics greatly improve the efficiency of the oxygen reduction reaction.
[0021] In the present invention, the heterogeneous bimetallic single atomic layers under the core-shell structure are coupled to each other for synergistic catalysis, which greatly improves the intrinsic catalytic activity of the carbon-based single atom catalyst. The ordered porous structure realizes a high specific surface area of the material and exposes more accessible atomic active sites. The porous microstructure improves the hydrophobic properties of the material surface, which is conducive to the formation of an effective "gas-liquid-solid" three-phase reaction interface and improves the output power density of the device. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is a flow chart for preparing ordered macroporous carbon-supported bimetallic single-atom catalysts in an embodiment of the present invention;
[0023] Figure 2 is a SEM image of IrFe-SACs in Example 1 of the present invention;
[0024] Figure 3 is a SEM image of CuFe-SACs in Example 2 of the present invention;
[0025] Figure 4 is a SEM image of CoFe-SACs in Comparative Example 1 of the present invention;
[0026] Figure 5are ORR performance curves of IrFe-SACs and other bimetallic atom catalysts in Examples 1-3 of the present invention and Comparative Example 1;
[0027] Figure 6 1 is a discharge capacity curve of liquid ZABs based on IrFe-SACs and Pt / C-RuO2 in an embodiment of the present invention;
[0028] Figure 7 The discharge polarization curve and power density curve of liquid ZABs based on IrFe-SACs and Pt / C-RuO2 in the embodiment of the present invention;
[0029] Figure 8 The liquid ZABs based on IrFe-SACs and Pt / C-RuO2 air cathode in the embodiment of the present invention are 5 mA cm -2 Constant current charge-discharge cycle curves under . DETAILED DESCRIPTION
[0030] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the following examples and drawings specifically illustrate the ordered macroporous carbon-supported bimetallic single-atom catalyst, preparation method and application of the present invention.
[0031] Example 1
[0032] A method for preparing an ordered macroporous carbon-supported iridium-iron bimetallic single-atom catalyst comprises the following steps:
[0033] S1, take 100mL of 5%wt polystyrene microsphere emulsion, microsphere diameter: ~500nm, in a centrifuge tube, centrifuge multiple times at 15000 rpm, remove the supernatant and place in a 60℃ oven to dry overnight to obtain a polystyrene sphere template. Dissolve 5.07g of 2-methylimidazole, 5.82g of zinc nitrate hexahydrate, and 0.505g of iridium acetylacetonate in 15mL of deionized water to form a precursor solution. Put the self-assembled polystyrene template into the above precursor solution and immerse it at room temperature for 2h to obtain product A.
[0034] S2, vacuum degas the product A for 30 minutes, then filter to obtain a polystyrene template and dry it in a 50°C oven overnight. The obtained polystyrene template is placed in a solution of ammonia water and methanol in a volume ratio of 1:1, vacuum degassing for 30 minutes, then immersed at room temperature for 24 hours, and the impregnated template is filtered to obtain the template, which is dried in a 50°C oven overnight to obtain a microsphere template filled with the precursor.
[0035] S3, placing the microsphere template filled with the precursor in an argon atmosphere of a tube furnace, heating it to 400°C at 5°C / min and calcining it for 5 hours, and then heating it to 920°C at 5°C / min and calcining it for 3 hours to obtain product B.
[0036] S4, 100 mg of product B was dispersed in 20 mL of ethanol to obtain dispersion A, and 50 mg of anhydrous ferric chloride, 500 mg of cyanuric acid, and 55 mg of dopamine hydrochloride were dispersed in 20 mL of ethanol and 10 mL of water to obtain dispersion B. Dispersion B was poured into dispersion A, and 750 μL of ammonia water was added and stirred at room temperature for aging for 12 h, and then centrifuged and dried, and then placed in an argon atmosphere of a tube furnace and heated to 800° C. at 5° C. / min and calcined for 2 hours to obtain the final product.
[0037] Example 2
[0038] Based on Example 1, this example replaces "0.505 g of iridium acetylacetonate" in step S1 with "0.25 g of copper nitrate trihydrate".
[0039] Example 3
[0040] Based on Example 1, this example replaces "0.505 g of iridium acetylacetonate" in step S1 with "0.30 g of nickel nitrate hexahydrate".
[0041] Comparative Example 1
[0042] Based on Example 1, this example replaces "0.505 g of iridium acetylacetonate" in step S1 with "0.30 g of cobalt nitrate hexahydrate".
[0043] Figure 1 It is a flow chart for preparing the ordered macroporous carbon-supported iridium-iron bimetallic single-atom catalyst in an embodiment of the present invention.
[0044] like Figure 1 As shown, the polystyrene microsphere template impregnated with the Ir-MOF precursor was pyrolyzed in an argon atmosphere to remove the microsphere template and carbonized to obtain a nitrogen-doped carbon support with honeycomb channels.
[0045] Figure 2 is a SEM image of IrFe-SACs in Example 1 of the present invention. Figure 3 is a SEM image of CuFe-SACs in Example 2 of the present invention. Figure 4 is a SEM image of CoFe-SACs in Comparative Example 1 of the present invention. Figure 5 It is the ORR performance curve of IrFe-SACs and other bimetallic atom catalysts in Example 3 of the present invention.
[0046] like Figure 2-5As shown, the corresponding carbon carrier can be prepared from MOF such as Co or Cu. Then, a layer of Fe complex is anchored on the surface of the porous nitrogen-doped carbon carrier by polydopamine, and a core-shell structure catalyst with a porous carbon layer anchored with Ir, Co or Cu single atoms and an outer carbon layer of Fe single atoms is obtained by high-temperature pyrolysis.
[0047] During the two-step pyrolysis, MOFs spontaneously aromatize at high temperatures to form Ir-N x / Fe-N x Highly graphitized nitrogen-doped carbon at single atomic sites. Zinc species evaporate at high temperatures and form a large number of micropores in the carbon matrix, which improves the dispersion of iridium-iron species and increases the specific surface area.
[0048] like Figure 5 As shown, the two transition metal single atoms are coupled to each other for synergistic catalysis, and IrFe-SACs exhibit excellent intrinsic catalytic activity for oxygen reduction reaction: high half-wave potential of oxygen reduction reaction: E 1 / 2 =0.872 V. IrFe-SACs catalyst, Zn foil and 6.0 M KOH containing 0.2 M zinc acetate were further used as the air positive electrode, negative electrode and electrolyte, respectively. Control ZABs were also prepared using Pt / C and RuO2 with a mass ratio of 1:1. The large reactive specific surface area of the ordered macroporous carbon structure provided abundant accessible active sites.
[0049] The optimized gas-liquid-solid three-phase interface of the hydrophobic porous carbon structure can achieve high discharge power density and capacity of zinc-air batteries, showing excellent battery performance.
[0050] Figure 6 It is the discharge specific capacity curve of liquid ZABs based on IrFe-SACs and Pt / C-RuO2 in the embodiment of the present invention.
[0051] like Figure 6 As shown, at 5 mA cm -2 The specific capacity of IrFe-SACs air cathode ZABs is 815.1 mAh g -1 , which is superior to Pt / C-RuO2 air cathode ZABs (733.4 mAh g -1 ).
[0052] Figure 7 These are the discharge polarization curves and power density curves of liquid ZABs based on IrFe-SACs and Pt / C-RuO2 in the embodiments of the present invention.
[0053] like Figure 7 As shown in Figure 2, the peak power density of ZABs based on IrFe-SACs is 219 mW cm -2, which is much higher than that of Pt / C-RuO2-based ZABs (114 mW cm -2 ).
[0054] Figure 8 The liquid ZABs based on IrFe-SACs and Pt / C-RuO2 air cathode in the embodiment of the present invention are 5 mA cm -2 Constant current charge-discharge cycle curves under .
[0055] like Figure 8 As shown, at 5 mA cm -2 The IrFe-SAC-based ZAB maintains constant charge (2.00 V) and discharge (1.12 V) voltages for more than 1650 cycles (greater than 550 h), indicating its excellent cycling durability.
[0056] Functions and Effects of the Embodiments
[0057] According to the ordered macroporous carbon-supported bimetallic single-atom catalyst, preparation method and application involved in the present invention, the composite structure of special bimetallic single atoms greatly enhances the intrinsic oxygen reduction reaction activity of the single-atom catalyst derived from the traditional zeolite imidazole framework (ZIF), the high specific surface area of the ordered hierarchical macroporous structure provides more accessible active sites, and the rich pore structure is more conducive to the formation of an effective three-phase interface and rapid mass transfer in the electrochemical process. These characteristics greatly improve the efficiency of the oxygen reduction reaction.
[0058] In the present invention, the heterogeneous bimetallic single atomic layers under the core-shell structure are coupled to each other for synergistic catalysis, which greatly improves the intrinsic catalytic activity of the carbon-based single atom catalyst. The ordered porous structure realizes a high specific surface area of the material and exposes more accessible atomic active sites. The porous microstructure improves the hydrophobic properties of the material surface, which is conducive to the formation of an effective "gas-liquid-solid" three-phase reaction interface and improves the output power density of the device.
[0059] The preparation method of the present invention has good process universality and can easily realize the preparation of carbon-based single-atom materials on the surface of air positive electrodes.
[0060] The ordered hierarchical macroporous carbon-supported bimetallic single-atom catalyst of the present invention has wide application potential in the fields of zinc-air batteries, fuel cells, etc. and has good application prospects.
[0061] The present invention selects 2-methylimidazole, zinc nitrate hexahydrate and iridium acetylacetonate to form a precursor solution, so that the catalyst has excellent intrinsic catalytic activity of oxygen reduction reaction.
[0062] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing an ordered macroporous carbon-supported bimetallic single-atom catalyst, characterized in that: The specific steps include: S1, synthesizing a polymer microsphere template, preparing a first transition metal-organic precursor solution, placing the polymer microsphere template into the first transition metal-organic precursor solution and immersing it at room temperature for 2 hours to obtain product A; S2, vacuum degassing the product A, then filtering and drying in a 40-60°C oven overnight, and vacuum degassing in a solution of ammonia water and methanol in a volume ratio of 1:(0.8-1.2) for 20-40 minutes, and then impregnating at room temperature for 20-30 hours, filtering to obtain an impregnated template, and drying in a 40-60°C oven overnight to obtain a microsphere template filled with a precursor; S3, placing the microsphere template filled with the precursor liquid in a tube furnace, introducing an inert gas, and calcining to obtain a product B; S4, mixing the product B with the second transition metal precursor liquid, aging, centrifuging, drying, placing in a tube furnace, introducing inert gas, heating to 600-1000° C. at 3-7° C. / min, and calcining for 2-4 hours.
2. The method for preparing the ordered macroporous carbon-supported bimetallic single-atom catalyst according to claim 1, characterized in that: in, The metal ions in the first transition metal-organic precursor and the second transition metal-organic precursor are selected from two or more of the transition metals cobalt, iron, zinc, iron, copper, nickel, manganese, platinum, ruthenium, and iridium, and the metal ion concentration is 60-200mmol / L. The first transition metal-organic precursor solution includes at least one of 2-methylimidazole, dopamine hydrochloride, pyrrole and dicyandiamide.
3. The method for preparing the ordered macroporous carbon-supported bimetallic single-atom catalyst according to claim 1, characterized in that: in, The polymer microsphere template is a polystyrene sphere template. The preparation method of the polystyrene sphere template is as follows: take 4-6%wt polystyrene microsphere emulsion into a centrifuge tube, centrifuge it for multiple times at a speed of 12000-18000 rpm, remove the supernatant and place it in a 40-80°C oven to dry overnight.
4. The method for preparing the ordered macroporous carbon-supported bimetallic single-atom catalyst according to claim 1, characterized in that: in, The calcination method in step S3 is to heat the mixture to 350-450° C. at 3-7° C. / min and calcine for 4-6 hours, and then heat the mixture to 900-940° C. at 3-7° C. / min and calcine for 2-4 hours.
5. The method for preparing the ordered macroporous carbon-supported bimetallic single-atom catalyst according to claim 1, characterized in that: in, The mixing and aging steps in step S4 are specifically as follows: the product B is dispersed in ethanol to obtain dispersion A, anhydrous ferric chloride, cyanuric acid, and dopamine hydrochloride are dispersed in ethanol and water to obtain dispersion B, dispersion B is poured into dispersion A, and after adding ammonia water, it is stirred and aged at room temperature for 10-14 hours, the mass ratio of the anhydrous ferric chloride, cyanuric acid and dopamine hydrochloride is 1:(9-11):(1-1.5), and the mass ratio of dispersion A to dispersion B is 1:(5-5.5).
6. The ordered macroporous carbon-supported bimetallic single-atom catalyst according to claim 1, characterized in that: The catalyst is prepared by the method for preparing the ordered macroporous carbon-supported bimetallic single-atom catalyst according to any one of claims 1 to 5.
7. The method for preparing the ordered macroporous carbon-supported bimetallic single-atom catalyst according to claim 1, characterized in that: in, It includes a three-dimensional porous nitrogen-doped carbon anchoring a first transition metal and a carbon-supported second transition metal single atomic layer coated on the surface of a three-dimensional porous nitrogen-doped carbon substrate. The three-dimensional porous nitrogen-doped carbon and the carbon-supported second transition metal single atomic layer have heterogeneous transition metal single atoms, and the inner and outer parts form a core-shell structure. The dual active metal atomic sites synergistically catalyze the oxygen reduction reaction.
8. Use of the ordered macroporous carbon-supported bimetallic single-atom catalyst as described in claims 6-7 in a zinc-air battery.
9. The use of the ordered macroporous carbon-supported bimetallic single-atom catalyst in a zinc-air battery according to claim 8, characterized in that: The zinc-air battery comprises a positive electrode sheet, a negative electrode sheet, a diaphragm, an air inlet and an electrolyte. The catalyst of the positive electrode sheet is the ordered macroporous carbon-supported bimetallic single-atom catalyst. The positive electrode sheet and the negative electrode sheet are arranged opposite to each other, and the positive electrode sheet and the negative electrode sheet are separated by the diaphragm. The positive electrode sheet has a side with the ordered macroporous carbon-supported bimetallic single-atom catalyst facing away from the air inlet.
10. The use of the ordered macroporous carbon-supported bimetallic single-atom catalyst in a zinc-air battery according to claim 9, characterized in that: The material of the negative electrode sheet is zinc foil, the separator is glass fiber paper, and the electrolyte is potassium hydroxide and zinc acetate aqueous solution.
Citation Information
Patent Citations
Carbon-loaded bimetallic monatomic catalyst and preparation method thereof
CN114522682A
Bimetal atom loaded porous carbon framework material as well as preparation method and application thereof
CN117059753A
Metal sulfide composite air electrode and preparation method and application thereof
CN117334930A
Carbon nanotube supported transition metal diatomic catalyst and preparation method thereof
CN117926274A
Preparation method of monatomic catalyst for regulating and controlling particle size of three-dimensional ordered pore structure carbon
CN118016915A
Cited By
Method for preparing metal monatomic material based on electron beam irradiation and application thereof
CN120459971A